High Young modulus lithium-aluminum-silicon substrate glass and chemically strengthened glass thereof

By controlling the oxide components and chemical reinforcement treatment, the problems of insufficient Young's modulus and production complexity of lithium-aluminum silicon glass are solved, and lithium-aluminum silicon substrate glass with high Young's modulus and acid resistance are achieved, which is suitable for high drop-resistant cover protection for electronic equipment.

CN119874184AActive Publication Date: 2025-04-25CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411933755.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-25
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The Young's modulus of existing lithium-aluminum silicon glass is insufficient, which cannot meet the high drop resistance requirements of cover protection glasses such as electronic equipment such as mobile phones. At the same time, its production costs are high, the process is complex and the repeatability is poor.

Method used

By controlling the content of oxide components, especially Y2O3 and La2O3, combined with chemical strengthening treatment, lithium-aluminum silicon-based glass with high Young's modulus and good acid resistance is prepared, and chemically strengthened glass with high stress is obtained through chemical strengthening.

Benefits of technology

The high Young's modulus (95GPa-130GPa) and good acid resistance of lithium-aluminum silicon-based glass have been achieved. The glass obtained after chemical reinforcement has high stress characteristics and is suitable for cover protection of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874184A_ABST
    Figure CN119874184A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium aluminum silicate glass, and provides lithium aluminum silicon base material glass with high Young's modulus and chemically strengthened glass of the lithium aluminum silicon base material glass, and the base material glass comprises the following components in percentage by mole of oxide: 60.0-70.0 mol% of SiO2; the content of Al2O3 is 8.0 to 15.0 mol%; 1.0 to 8.0 mol% of MgO; 7.0 to 12.0 mol% of Li2O; 2.0 to 5.0 mol% of Na2O; and Y2O3, and La2O3; wherein the content of Y2O3 and La2O3 is 4.0 to 8.0 mol percent; the chemically strengthened glass is obtained by chemically strengthening base material glass. The base material glass and the chemically strengthened glass are reasonable in component content, a good combination effect is exerted, the components are matched, so that the formed glass has high Young modulus, high stress performance and good acid resistance, meanwhile, the glass has good mass production performance, and the development requirement of cover plate protection glass in high-end mobile phone products can be met.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application submitted to the China Patent Office on October 19, 2023, with application number 202311355205.7 and invention name "Lithium aluminum silicon substrate glass with high Young's modulus and chemically strengthened glass thereof". Technical Field

[0002] The present application relates to the technical field of lithium aluminum silicate glass, and in particular to a lithium aluminum silicate substrate glass with a high Young's modulus and a chemically strengthened glass thereof. Background Art

[0003] The cover protective glass of electronic devices needs to have high drop resistance. Since its birth, microcrystalline glass has been able to meet the requirements of high drop resistance due to its high Young's modulus (about 100GPa) and high stress performance, and can be widely used in cover protective glass of electronic devices such as mobile phones. However, the raw materials for the production of microcrystalline glass contain a high content of lithium oxide, so the manufacturing cost is very high, resulting in the high price of microcrystalline glass; in addition, the production process of microcrystalline glass is complicated, and a nucleation-crystallization step is required, resulting in large fluctuations in the yield of the finished product and poor repeatability. At present, the raw material cost of lithium aluminum silicate glass products is low, and no crystallization step is required. The processing technology is simpler than that of microcrystalline glass, and it has obvious production advantages; but the Young's modulus of lithium aluminum silicate glass is only about 80GPa, and the drop resistance cannot be compared with the drop resistance of microcrystalline glass, which is difficult to meet the development needs of cover protective glass for electronic devices such as mobile phones.

[0004] In the prior art, the Young's modulus of lithium aluminum silicate glass has been significantly improved by adding dense oxides such as yttrium oxide, lanthanum oxide, niobium oxide, etc.; however, directly adding dense oxides such as yttrium oxide, lanthanum oxide, niobium oxide, etc. will lead to a decrease in the amount of ion exchange, thereby causing a decrease in the surface stress level of the glass, and thus the improvement in the drop resistance is limited; in addition, the addition of the above-mentioned dense oxides will also increase the crystallization temperature of the glass, making it easy to crystallize at a lower viscosity, thereby making the production and molding of the glass difficult, resulting in problems such as poor mass production. Summary of the invention

[0005] Based on the above situation, the purpose of the present application is to solve the shortcomings of the existing technical solutions and provide a lithium aluminum silicon substrate glass that has good acid resistance and high Young's modulus and can be mass-produced. In addition, the lithium aluminum silicon substrate glass can be chemically strengthened to obtain chemically strengthened glass with high stress.

[0006] In a first aspect, the present application provides a lithium aluminum silicon substrate glass, wherein the substrate glass comprises the following components in terms of molar percentage of oxides:

[0007] SiO2 60.0-70.0mol%;

[0008] Al2O3 8.0-15.0mol%;

[0009] MgO 1.0-8.0 mol%;

[0010] Li2O 7.0-12.0mol%;

[0011] Na2O 2.0-5.0mol%;

[0012] and Y2O3 and La2O3;

[0013] Among them, Y2O3+La2O3 is 4.0-8.0 mol%.

[0014] In some embodiments of the present application, in terms of molar percentage of oxides, the SiO2 is 63.0-70.0 mol%, preferably 63.0-67.0 mol%; and / or the Al2O3 is 8.0-13.0 mol%, preferably 9.0-12.0 mol%.

[0015] In some embodiments of the present application, in the substrate glass, Al2O3 / SiO2≤0.2, measured in molar percentage of oxides.

[0016] In some embodiments of the present application, in terms of molar percentage of oxides, Y2O3+La2O3 in the substrate glass is 5.0-7.0 mol%.

[0017] In some embodiments of the present application, in the substrate glass, La2O3 / (Y2O3+La2O3) is 0.25-0.7, and La2O3 / (Y2O3+La2O3) is preferably 0.4-0.7, calculated as a molar percentage of oxides.

[0018] In some embodiments of the present application, the substrate glass further comprises the following components, measured in molar percentage of oxides:

[0019] K2O 0-2.0mol%;

[0020] ZrO2 0-2.0mol%;

[0021] B2O3 0-5.0mol%;

[0022] P2O5 0-5.0mol%;

[0023] CaO 0-8.0 mol%;

[0024] SrO 0-3.0 mol%.

[0025] In some embodiments of the present application, the Young's modulus of the substrate glass is 95 GPa-130 GPa, preferably 96 GPa-120 GPa.

[0026] In some embodiments of the present application, the bifurcation threshold of the substrate glass is 49000MPa / mm-60000MPa / mm, preferably 50000MPa / mm-58000MPa / mm.

[0027] In some embodiments of the present application, the upper crystallization temperature limit of the substrate glass is 1100°C-1330°C.

[0028] In some embodiments of the present application, the viscosity of the substrate glass corresponding to the upper limit temperature of crystallization is 10 2.2 dPa·s or more, preferably 10 2.5 dPa·s or above.

[0029] In some embodiments of the present application, the substrate glass is etched in a 5 wt % HCl solution at 95° C. for 24 h, and the erosion amount is ≤7 mg / cm 2 .

[0030] In a second aspect, the present application provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by chemically strengthening the substrate glass as described above.

[0031] In some embodiments of the present application, chemical strengthening of the substrate glass includes single-step chemical strengthening or multi-step chemical strengthening.

[0032] In some embodiments of the present application, the single-step chemical strengthening uses a salt bath containing NaNO 3 , and preferably the content of NaNO 3 in the salt bath is 30-100 wt %.

[0033] In some embodiments of the present application, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.

[0034] In some embodiments of the present application, the temperature of the single-step chemical strengthening is 380° C.-500° C., and more preferably, the ion exchange time of the single-step chemical strengthening is 3 h-10 h.

[0035] In some embodiments of the present application, the multi-step chemical strengthening includes two-step chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 in the salt bath is 70-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, and preferably the content of KNO3 in the salt bath is 60-100wt%.

[0036] In some embodiments of the present application, the multi-step chemical strengthening includes two-step chemical strengthening, the first step of chemical strengthening using a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 in the mixed salt bath is 70-100wt%, and the content of KNO3 is 0-30wt%; the second step of chemical strengthening using a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.

[0037] In some embodiments of the present application, the temperature of the first step of chemical strengthening is 380° C.-500° C., and the preferred ion exchange time is 3 h-10 h.

[0038] In some embodiments of the present application, the temperature of the second step chemical strengthening is 380° C.-500° C., and the preferred ion exchange time is 1 h-10 h.

[0039] In some embodiments of the present application, the CS_50 of the chemically strengthened glass is 100 MPa-150 MPa; preferably, the CS_50 is 105 MPa-150 MPa; more preferably, the CS_50 is 110 MPa-140 MPa.

[0040] In some embodiments of the present application, DOL_0 of the chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the chemically strengthened glass.

[0041] In some embodiments of the present application, the CT_LD of the chemically strengthened glass is 45000 MPa / mm-60000 MPa / mm, preferably, the CT_LD value is 45000 MPa / mm-57000 MPa / mm.

[0042] In a third aspect, the present application provides a method for preparing the chemically strengthened glass as described above, comprising the following steps:

[0043] (1) selecting raw material components according to the composition of the substrate glass, mixing them, melting and forming them, and then cooling and annealing them to obtain the substrate glass;

[0044] (2) Chemically strengthening the base glass to obtain chemically strengthened glass.

[0045] In some embodiments of the present application, the chemical strengthening includes single-step chemical strengthening or multi-step chemical strengthening.

[0046] In some embodiments of the present application, the single-step chemical strengthening uses a salt bath containing NaNO 3 , and preferably the content of NaNO 3 in the salt bath is 30-100 wt %.

[0047] In some embodiments of the present application, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.

[0048] In some embodiments of the present application, the temperature of the single-step chemical strengthening is 380° C.-500° C., and more preferably, the ion exchange time of the single-step chemical strengthening is 3 h-10 h.

[0049] In some embodiments of the present invention, the multi-step chemical strengthening includes two-step chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 in the salt bath is 70-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, and preferably the content of KNO3 in the salt bath is 60-100wt%.

[0050] In some embodiments of the present application, the multi-step chemical strengthening includes two-step chemical strengthening, the first step of chemical strengthening using a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 in the mixed salt bath is 70-100wt%, and the content of KNO3 is 0-30wt%; the second step of chemical strengthening using a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.

[0051] In some embodiments of the present application, the temperature of the first step of chemical strengthening is 380° C.-500° C., and the preferred ion exchange time is 3 h-10 h.

[0052] In some embodiments of the present application, the temperature of the second step chemical strengthening is 380° C.-500° C., and the preferred ion exchange time is 1 h-10 h.

[0053] In a fourth aspect, the present application provides a glass device, which includes the above-mentioned lithium aluminum silicon base glass or the above-mentioned chemically strengthened glass.

[0054] In a fifth aspect, the present application provides an electronic device, which includes the above-mentioned lithium aluminum silicon substrate glass or the above-mentioned chemically strengthened glass.

[0055] In some embodiments of the present application, the electronic device includes one or more of a mobile phone, a tablet computer, a smart wearable device, a display, or a television.

[0056] Compared with the prior art, this application has the following beneficial effects:

[0057] 1. The present application controls the Y2O3+La2O3 to be between 4-8 mol% to control the lithium aluminum silicon substrate glass to have a high Young's modulus and good acid resistance; the substrate glass has high stress characteristics after chemical strengthening.

[0058] 2. The present application controls SiO2>60mol% and Al2O3<17mol% to control the lithium aluminum silicon substrate glass to have good acid resistance. Adding ZrO2 can further improve the acid resistance of the lithium aluminum silicon substrate glass.

[0059] 3. The present invention controls La2O3 / (Y2O3+La2O3)≥0.25, preferably ≥0.4; so that the upper limit crystallization temperature of the lithium aluminum silicon substrate glass is 1100℃-1330℃, and the viscosity corresponding to the upper limit crystallization temperature is 10 2.2 dPa·s or more; thus having mass production characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 Schematic diagram of the stress release device for the immediate fracture test; in the figure: 1-height adjustment rail, 2-start adjustment rail, 3-pressing head, 4-chemically strengthened glass sample.

[0061] Figure 2 This is the crack damage state diagram of the immediate fracture test.

[0062] Figure 3 This is a schematic diagram of placing a long quartz tank in a gradient furnace for this application. DETAILED DESCRIPTION

[0063] This application will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by those skilled in the art based on this application belong to the scope of protection of this application.

[0064] The relevant special terms involved in this application are explained as follows.

[0065] In the present application, substrate glass refers to a glass matrix material that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.

[0066] In this application, chemically strengthened glass refers to strengthened glass that has been treated by a high-temperature ion exchange process. In a high-temperature salt bath, alkali metal ions with large ion radius (such as potassium ions and sodium ions) replace alkali metal ions with small ion radius (such as sodium ions and lithium ions) in the glass, thereby generating an exchange ion volume difference, generating high to low compressive stress from the surface to the inside of the substrate glass, hindering and delaying the expansion of microcracks in the glass, and achieving the purpose of improving the mechanical strength of the glass.

[0067] In this application, surface CS refers to surface compressive stress or surface compression stress. After the substrate glass is chemically strengthened, the alkali metal ions with smaller surface radius (such as sodium ions and lithium ions) are replaced by alkali metal ions with larger radius (such as potassium ions and sodium ions). Due to the crowding effect of the alkali metal ions with larger radius, compressive stress is generated on the glass surface. It can be measured by the stress meter FSM-6000 of Japan Orihara.

[0068] In this application, CS_50: CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface.

[0069] In this application, DOL_0: depth of compressive stress layer, also called compressive stress layer depth, refers to the distance from any surface of glass to the position where the compressive stress near the surface is zero. It can be measured by the stress meter SLP-2000 of Japan Orihara.

[0070] In the present application, CT_LD refers to the ratio of the definite integral of the tensile stress curve of chemically strengthened glass to the thickness of the chemically strengthened glass, which is recorded as the tensile stress linear density. The substrate glass is placed in a salt bath for ion exchange to form a strengthening layer (i.e., a compressive stress layer). During the ion exchange process, a tensile stress layer is formed inside the glass, and the tensile stress layer has an upper boundary that is spaced a certain distance from the upper surface of the chemically strengthened glass and a lower boundary that is spaced a certain distance from the lower surface of the chemically strengthened glass. The tensile stress at a point on a line segment in the tensile stress layer that is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively is recorded as the tensile stress curve, and the ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened glass is recorded as the tensile stress linear density, which is the ratio of the sum of the tensile stresses of the chemically strengthened glass measured by the SLP-2000 stress meter to the glass thickness.

[0071] In this application, CT_LD max Refers to the maximum value of tensile stress line density. The maximum tensile stress line density (CT_LD) value that can be obtained by ion exchange chemical strengthening of substrate glass under specific salt bath conditions is the maximum tensile stress line density CT_LD that can be obtained by substrate glass under the salt bath conditions. max This data can characterize the strengthenability / ion exchangeability of the substrate glass.

[0072] In the present application, the bifurcation threshold refers to the minimum tensile stress linear density value of the chemically strengthened glass prepared from a certain formula substrate glass when the glass crack bifurcates in an immediate fracture test, that is, the bifurcation threshold of the chemically strengthened glass prepared from the formula substrate glass.

[0073] In a first aspect, the present application provides a lithium aluminum silicon substrate glass, wherein the substrate glass comprises the following components in terms of molar percentage of oxides:

[0074] SiO2 60.0-70.0mol%;

[0075] Al2O3 8.0-15.0mol%;

[0076] MgO 1.0-8.0 mol%;

[0077] Li2O 7.0-12.0mol%;

[0078] Na2O 2.0-5.0mol%;

[0079] ZrO2 0.3-2.0mol%;

[0080] and Y2O3 and La2O3;

[0081] Among them, Y2O3+La2O3 is 4.0-8.0 mol%.

[0082] In the present application, SiO2 is a necessary component constituting the glass skeleton. A high content of SiO2 can ensure that the glass has excellent properties such as high strength, resistance to thermal expansion, and chemical stability. However, the stability of the skeleton has little effect on improving the density of the glass, so it has a general effect on the Young's modulus and mechanical strength of the glass. Since SiO2 has a tendency to increase the viscosity of the glass melt, an excessively high content of SiO2 will make the glass difficult to melt and form, thereby increasing the difficulty of melting and production of the glass. In some embodiments of the present application, the substrate glass described in the present application includes 60.0-70.0 mol% of SiO2, measured in mole percentage of oxides. In some embodiments of the present application, the substrate glass includes 63.0-70.0 mol% of SiO2, preferably 63.0-67.0 mol% of SiO2, measured in mole percentage of oxides. In some embodiments of the present application, the content of SiO2 in the substrate glass can be 60.0 mol%, 61.0 mol%, 62.0 mol%, 63.0 mol%, 63.10 mol%, 64.0 mol%, 64.50 mol%, 65.0 mol%, 66.0 mol%, 67.0 mol%, 68.0 mol%, 69.0 mol%, 70.0 mol% or a value within the range formed by any two of the above values ​​as endpoints.

[0083] Al2O3 forms aluminum-oxygen tetrahedrons in the glass and connects the non-bridging oxygen in the silicon-oxygen network structure, which can increase the strength of the network structure and further enhance the strength, structural stability and chemical stability of the glass. In the lithium aluminum-silicon glass system, the chemical stability of Al2O3 is not as good as SiO2, such as acid resistance. When the proportion of Al2O3 in the network structure increases, the acid resistance of the glass will decrease; and Al2O3 is the main component of the lithium aluminum-silicon glass system that forms its crystallization phase spodumene. The addition of excessive Al2O3 will quickly increase the crystallization tendency of the glass and increase the difficulty of glass melting, thereby increasing the difficulty and cost of glass production. In some embodiments of the present application, the substrate glass described in the present application includes 8.0-15.0 mol% of Al2O3 in terms of molar percentage of oxides. In some embodiments of the present application, the substrate glass includes 8.0-13.0 mol% of Al2O3 in terms of molar percentage of oxides, preferably 9.0-12.0 mol% of Al2O3. In some embodiments of the present application, the content of Al2O3 in the substrate glass can be 8.0mol%, 8.5mol%, 9.0mol%, 9.5mol%, 10.0mol%, 10.5mol%, 11.0mol%, 11.5mol%, 12.0mol%, 12.5mol%, 13.0mol%, 13.5mol%, 14.0mol%, 14.5mol%, 15.0mol% or a value within the range formed by any two of the above values ​​as endpoints.

[0084] The present application adopts alkaline earth metal oxide MgO as the network outer body of glass, which can adjust the viscosity-temperature performance of glass, thereby improving the melting performance of glass. In some embodiments of the present application, the substrate glass of the present application includes 1.0-8.0 mol% of MgO in terms of molar percentage of oxide. In some embodiments of the present application, the content of MgO in the substrate glass can be 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol%, 5.5 mol%, 6.0 mol%, 6.5 mol%, 7.0 mol%, 7.5 mol%, 8.0 mol% or a value within the range formed by any two of the above values ​​as endpoints.

[0085] Li2O, as an alkali metal component of the glass network, breaks the silicon-oxygen network of the glass, forms a large amount of non-bridging oxygen, makes the structure of the glass loose, and can greatly reduce the melting temperature and forming temperature of the glass. At the same time, the alkali metal ions in Li2O make the glass have the possibility of ion exchange strengthening. In some embodiments of the present application, the substrate glass described in the present application includes 7.0-12.0 mol% Li2O in terms of molar percentage of oxide. In some embodiments of the present application, the content of Li2O in the substrate glass can be 7.0 mol%, 7.5 mol%, 8.0 mol%, 8.5 mol%, 9.0 mol%, 9.5 mol%, 10.0 mol%, 10.5 mol%, 11.0 mol%, 11.5 mol%, 12.0 mol% or a value within the range formed by any two of the above values ​​as endpoints.

[0086] Na2O, as an alkali metal component of the glass network, breaks the silicon-oxygen network of the glass and forms a large amount of non-bridging oxygen, making the structure of the glass loose, which can greatly reduce the melting temperature and forming temperature of the glass; at the same time, the alkali metal ions in Na2O make the glass possible to be strengthened by ion exchange. In some embodiments of the present application, the substrate glass described in the present application includes 2.0-5.0 mol% Na2O in terms of molar percentage of oxide. In some embodiments of the present application, the content of Na2O in the substrate glass can be 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol% or a value within the range formed by any two of the above values ​​as endpoints.

[0087] The present application uses Y2O3 and La2O3 as network modification components of glass, which can reduce the high-temperature viscosity of glass, facilitate glass melting and eliminate intrinsic defects; can improve the Young's modulus and micro-Vickers hardness of glass, and at the same time can improve the chemical strengthening performance of glass, and improve the stress effect of unit ion exchange of chemically strengthened glass. In addition, when Y2O3 and La2O3 are mixed and added to lithium aluminum silicate glass in the present application, the crystallization tendency of lithium aluminum silicate glass is less than the crystallization tendency of Y2O3 or La2O3 alone. From the perspective of balancing high Young's modulus and crystallization tendency, the content of Y2O3+La2O3 is controlled within a reasonable range. In some embodiments of the present application, in terms of molar percentage of oxides, the substrate glass described in the present application includes Y2O3 and La2O3, and the content of Y2O3+La2O3 is 4.0-8.0mol%, preferably 5.0-7.0mol%. In some embodiments of the present application, the content of Y2O3+La2O3 in the substrate glass can be 4.0 mol%, 4.5 mol%, 5.0 mol%, 5.5 mol%, 6.0 mol%, 6.5 mol%, 7.0 mol%, 7.5 mol%, 8.0 mol% or a value within a range formed by any two of the above values ​​as endpoints.

[0088] In some embodiments of the present application, the substrate glass includes 2.0-5.0 mol% Y2O3 in terms of molar percentage of oxide. In some embodiments of the present application, the content of Y2O3 in the substrate glass may be 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0089] In some embodiments of the present application, the substrate glass includes 2.0-5.0 mol% La2O3 in terms of molar percentage of oxide. In some embodiments of the present application, the content of La2O3 in the substrate glass may be 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0090] In the present application, the content of La2O3 cannot be too high, because if it tends to the same dense oxide alone, the tendency of crystallization will suddenly increase, and Y2O3 is more conducive to improving the stress effect than La2O3. From the perspective of balancing crystallization and high stress performance, the present application controls the value of La2O3 / (Y2O3+La2O3) within a suitable range. In some embodiments of the present application, in terms of molar percentage of oxide, La2O3 / (Y2O3+La2O3) in the substrate glass is 0.25-0.70, preferably 0.40-0.70. In some embodiments of the present application, the value of La2O3 / (Y2O3+La2O3) in the substrate glass can be 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70 or a value within the range formed by any two of the above values ​​as endpoints.

[0091] In some embodiments of the present application, in terms of molar percentage of oxides, in the substrate glass, Al2O3 / SiO2≤0.2. In some embodiments of the present application, the value of Al2O3 / SiO2 in the substrate glass may be 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a value within a range formed by any two of the above values ​​as endpoints.

[0092] In some embodiments of the present application, the substrate glass includes 0-2.0 mol% K2O in terms of molar percentage of oxide. In some embodiments of the present application, the content of K2O in the substrate glass may be 0.0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints. K2O, as a network exo-alkali metal component of the glass, breaks the silicon-oxygen network of the glass, forms a large amount of non-bridging oxygen, makes the structure of the glass loose, and can significantly reduce the melting temperature and forming temperature of the glass.

[0093] In some embodiments of the present application, the substrate glass includes 0-2.0 mol% ZrO2 in terms of molar percentage of oxide. In some embodiments of the present application, the content of ZrO2 in the substrate glass may be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0094] In some embodiments of the present application, the substrate glass includes 0-5.0 mol% B2O3 in terms of molar percentage of oxide. In some embodiments of the present application, the content of B2O3 in the substrate glass may be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.50 mol%, 5.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0095] In some embodiments of the present application, the substrate glass includes 0-5.0 mol% of P2O5 in terms of molar percentage of oxide. In some embodiments of the present application, the content of P2O5 in the substrate glass can be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.50 mol%, 5.0 mol% or a value within a range formed by any two of the above values ​​as endpoints. P2O5 is a component that constitutes a network, which can reduce the difficulty of melting glass and increase the ion diffusion rate of chemical strengthening, but it will reduce the chemical durability of the glass, and it is easy to cause the glass to phase separate and the devitrification temperature to be reduced.

[0096] In some embodiments of the present application, the substrate glass includes 0-8.0 mol% of CaO in terms of molar percentage of oxide. In some embodiments of the present application, the content of CaO in the substrate glass may be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol%, 5.0 mol%, 5.5 mol%, 6.0 mol%, 6.5 mol%, 7.0 mol%, 7.5 mol%, 8.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0097] In some embodiments of the present application, the substrate glass includes 0-3.0 mol% SrO in terms of molar percentage of oxide. In some embodiments of the present application, the content of SrO in the substrate glass may be 0 mol%, 0.5 mol%, 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, or a value within a range formed by any two of the above values ​​as endpoints.

[0098] In some embodiments of the present application, the Young's modulus of the substrate glass is 95 GPa-130 GPa, preferably 96 GPa-120 GPa. In some embodiments of the present application, the Young's modulus of the substrate glass may be 95 GPa, 96 GPa, 97 GPa, 98 GPa, 99 GPa, 100 GPa, 101 GPa, 102 GPa, 103 GPa, 104 GPa, 105 GPa, 106 GPa, 107 GPa, 108 GPa, 109 GPa, 110 GPa, 111 GPa, 112 GPa, 113 GPa, 114 GPa, 115 GPa, 116 GPa, 117 GPa, 118 GPa, 119 GPa, 120 GPa, or a value within a range formed by any two of the above values ​​as endpoints. The present application has no particular limitation on the test method and test instrument of Young's modulus, as long as the purpose of the present application can be achieved, for example, the test is performed using an ultrasonic method.

[0099] In some embodiments of the present application, the bifurcation threshold of the substrate glass is 49000MPa / mm-60000MPa / mm, preferably 50000MPa / mm-58000MPa / mm. In some embodiments of the present application, the bifurcation threshold of the chemically strengthened glass may be 49000MPa / mm, 49500MPa / mm, 50000MPa / mm, 50500MPa / mm, 51000MPa / mm, 51500MPa / mm, 52000MPa / mm, 52500MPa / mm, 53000MPa / mm, 53500MPa / mm, 54000MPa / mm, 54500MPa / mm, 550 ... 500 MPa / mm, 55000 MPa / mm, 55500 MPa / mm, 56000 MPa / mm, 56500 MPa / mm, 57000 MPa / mm, 57500 MPa / mm, 58000 MPa / mm, 58500 MPa / mm, 59000 MPa / mm, 59500 MPa / mm, 60000 MPa / mm or a value within the range formed by any two of the above values ​​as endpoints.

[0100] In some embodiments of the present application, the crystallization upper limit temperature of the substrate glass is 1100-1330° C. In some embodiments of the present application, the value of the crystallization upper limit temperature can be 1100° C., 1110° C., 1120° C., 1130° C., 1140° C., 1150° C., 1160° C., 1170° C., 1180° C., 1190° C., 1200° C., 1210° C., 1220° C., 1230° C., 1240° C., 1250° C., 1260° C., 1270° C., 1280° C., 1290° C., 1300° C., 1310° C., 1320° C., 1330° C., or a value within the range formed by any two of the above values ​​as endpoints.

[0101] In some embodiments of the present application, the viscosity of the substrate glass corresponding to the upper limit temperature of crystallization is 10 2.2 dPa·s or more, preferably 10 2.5 In some embodiments of the present application, the viscosity corresponding to the upper limit temperature of crystallization may be 10 2.2 dPa·s, 10 2.3 dPa·s, 10 2.4 dPa·s, 10 2.5 dPa·s, 10 2.6 dPa·s, 10 2.7 dPa·s, 10 2.8 dPa·s, 10 2.9 dPa·s, 10 3.0 dPa·s, 10 3.1 dPa·s or a value within a range formed by any two of the above values ​​as endpoints.

[0102] In some embodiments of the present application, the substrate glass is etched in a 5 wt % HCl solution at 95° C. for 24 h, and the erosion amount is ≤7 mg / cm 2 In some embodiments of the present application, the erosion amount of the substrate glass after being etched in a 5 wt % HCl solution at 95° C. for 24 hours may be 0.2 mg / cm 2 , 0.3mg / cm 2 , 0.5mg / cm 2 , 1.0mg / cm 2 , 1.5mg / cm 2 , 2.0mg / cm 2 , 2.5mg / cm 2 、3.0mg / cm 2 、3.5mg / cm 2 , 4.0mg / cm 2 , 4.5mg / cm 2 , 5.0mg / cm 2, 5.5mg / cm 2 、6.0mg / cm 2 、6.5mg / cm 2 、7.0mg / cm 2 Or a value within a range formed by any two of the above values ​​as endpoints. The present application has no particular limitation on the test method and test instrument for the erosion of the substrate glass after immersion in a 5wt% HCl solution at 95°C for 24 hours, as long as the purpose of the present application can be achieved.

[0103] In a second aspect, the present application provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by chemically strengthening the substrate glass as described above.

[0104] In some embodiments of the present application, chemical strengthening of the substrate glass includes single-step chemical strengthening or multi-step chemical strengthening.

[0105] In some embodiments of the present application, the single-step chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 in the salt bath is 30-100wt%. In some embodiments of the present application, the content of NaNO3 in the salt bath can be 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0106] In some embodiments of the present application, the single-step chemical strengthening adopts a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%. In some embodiments of the present application, the content of KNO3 in the mixed salt bath can be 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the content of NaNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0107] In some embodiments of the present application, the temperature of the single-step chemical strengthening is 380°C-500°C, and more preferably the ion exchange time of the single-step chemical strengthening is 3h-10h. In some embodiments of the present application, the temperature of the single-step chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the single-step chemical strengthening can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0108] In some embodiments of the present invention, the multi-step chemical strengthening includes two-step chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 in the salt bath is 70-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 in the salt bath is 60-100wt%. In some embodiments of the present application, the content of NaNO3 in the salt bath can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the content of KNO3 in the salt bath can be 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0109] In some embodiments of the present application, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 in the mixed salt bath is 70-100wt%, and the content of KNO3 is 0-30wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%. In some embodiments of the present application, in the first step of chemical strengthening, the content of NaNO3 in the mixed salt bath can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt%, or a value within the range formed by any two of the above values ​​as endpoints; the content of KNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, in the second step of chemical strengthening, the content of KNO3 in the mixed salt bath can be 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints; the content of NaNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0110] In some embodiments of the present application, the temperature of the first step of chemical strengthening is 380°C-500°C, and the preferred ion exchange time is 3h-10h. In some embodiments of the present application, the temperature of the first step of chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the first step of chemical strengthening can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0111] In some embodiments of the present application, the temperature of the second step chemical strengthening is 380°C-500°C, and the preferred ion exchange time is 1h-10h. In some embodiments of the present application, the temperature of the second step chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the second step chemical strengthening can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0112] In some embodiments of the present application, the CS_50 of the chemically strengthened glass is 100MPa-150MPa, preferably 105MPa-150MPa, and more preferably 110MPa-140MPa. In some embodiments of the present application, the CS_50 value of the chemically strengthened glass can be 100MPa, 110MPa, 120MPa, 130MPa, 140MPa, 150MPa, or a value within the range formed by any two of the above values ​​as endpoints. The present application does not specifically limit the test method and test instrument for the surface CS_50, as long as the purpose of the present application can be achieved, for example, it can be measured by a stress meter FSM-6000.

[0113] In the present application, the thickness of the glass changes very little before and after chemical strengthening, which is almost negligible, that is, the thickness of the substrate glass is very different from the thickness of the chemically strengthened glass obtained by chemically strengthening the substrate glass. In some embodiments of the present application, the depth of the surface stress layer DOL_0 of the chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the chemically strengthened glass. In some embodiments of the present application, the value of the surface stress layer depth DOL_0 of the chemically strengthened glass can be 0.14t, 0.145t, 0.15t, 0.155t, 0.16t, 0.165t, 0.17t, 0.175t, 0.18t, 0.185t, 0.19t, 0.195t, 0.20t, 0.205t, 0.21t, 0.215t, 0.22t, 0.225t, 0.230t, 0.235t, 0.24t, 0.245t, 0.25t or a value within the range formed by any two of the above values ​​as endpoints.

[0114] The thickness of the chemically strengthened glass described in the present application is not particularly limited, and can be, for example, 0.4-2.0 mm. The thickness of the chemically strengthened glass described in the present application can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a value within a range formed by any two of the above values ​​as endpoints.

[0115] In some embodiments of the present application, the CT_LD of the chemically strengthened glass is 45000MPa / mm-60000MPa / mm, preferably 45000MPa / mm-57000MPa / mm. In some embodiments of the present application, the CT_LD value of the chemically strengthened glass can be 45000MPa / mm, 46000MPa / mm, 47000MPa / mm, 48000MPa / mm, 49000MPa / mm, 50000MPa / mm, 51000MPa / mm, 52000MPa / mm, 53000MPa / mm, 54000MPa / mm, 55000MPa / mm, 56000MPa / mm, 57000MPa / mm, 58000MPa / mm, 59000MPa / mm, 60000MPa / mm or a value within the range formed by any two of the above values ​​as endpoints. The present application does not impose any particular limitation on the testing equipment and testing method for CT_LD of chemically strengthened glass, as long as the purpose of the present application can be achieved.

[0116] In a third aspect, the present application provides a method for preparing the chemically strengthened glass as described above, comprising the following steps:

[0117] (1) selecting raw material components according to the composition of the substrate glass, mixing them, melting and forming them, and then cooling and annealing them to obtain the substrate glass;

[0118] (2) Chemically strengthening the base glass to obtain chemically strengthened glass.

[0119] In some embodiments of the present application, chemical strengthening of the substrate glass includes single-step chemical strengthening or multi-step chemical strengthening.

[0120] In some embodiments of the present application, the single-step chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 in the salt bath is 30-100wt%. In some embodiments of the present application, the content of NaNO3 in the salt bath can be 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0121] In some embodiments of the present application, the single-step chemical strengthening adopts a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%. In some embodiments of the present application, the content of KNO3 in the mixed salt bath can be 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the content of NaNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0122] In some embodiments of the present application, the temperature of the single-step chemical strengthening is 380°C-500°C, and more preferably the ion exchange time of the single-step chemical strengthening is 3h-10h. In some embodiments of the present application, the temperature of the single-step chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the single-step chemical strengthening can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0123] In some embodiments of the present invention, the multi-step chemical strengthening includes two-step chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 in the salt bath is 70-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 in the salt bath is 60-100wt%. In some embodiments of the present application, the content of NaNO3 in the salt bath in the first step of chemical strengthening can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the content of KNO3 in the salt bath in the second step of chemical strengthening can be 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0124] In some embodiments of the present application, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 in the mixed salt bath is 70-100wt%, and the content of KNO3 is 0-30wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%. In some embodiments of the present application, in the first step of chemical strengthening, the content of NaNO3 in the mixed salt bath can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt%, or a value within the range formed by any two of the above values ​​as endpoints; the content of KNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, in the second step of chemical strengthening, the content of KNO3 in the mixed salt bath can be 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or a value within the range formed by any two of the above values ​​as endpoints; the content of NaNO3 in the mixed salt bath can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt% or a value within the range formed by any two of the above values ​​as endpoints.

[0125] In some embodiments of the present application, the temperature of the first step of chemical strengthening is 380°C-500°C, and the preferred ion exchange time is 3h-10h. In some embodiments of the present application, the temperature of the first step of chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the first step of chemical strengthening can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0126] In some embodiments of the present application, the temperature of the second step chemical strengthening is 380°C-500°C, and the preferred ion exchange time is 1h-10h. In some embodiments of the present application, the temperature of the second step chemical strengthening can be 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 500°C, or a value within the range formed by any two of the above values ​​as endpoints. In some embodiments of the present application, the ion exchange time of the second step chemical strengthening can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a value within the range formed by any two of the above values ​​as endpoints.

[0127] In a fourth aspect, the present application provides a glass device, which includes the above-mentioned lithium aluminum silicon base glass or the above-mentioned chemically strengthened glass.

[0128] In a fifth aspect, the present application provides an electronic device, which includes the above-mentioned lithium aluminum silicon substrate glass or the above-mentioned chemically strengthened glass.

[0129] In some embodiments of the present application, an electronic device includes: a housing, the housing including a front surface, a rear surface and a side surface; and an electronic component partially located within the housing, the electronic component including a display, which is located at the front surface of the housing or adjacent to the front surface; the front surface and / or the rear surface and / or the side surface include the chemically strengthened glass as described above in the present application.

[0130] In some embodiments of the present application, the electronic device further includes a covering product covering the front surface of the housing or located on the display, wherein the covering product includes the chemically strengthened glass as described above in the present application.

[0131] In some embodiments of the present application, the electronic device includes a mobile phone, a tablet computer, a smart wearable device, a display or a television, etc.; wherein the smart wearable device includes a smart bracelet, a smart watch and smart glasses, etc., and the display includes a high-definition display, a car display, an aircraft display, etc.

[0132] The various glasses in this application were tested using the following methods:

[0133] Young's modulus test

[0134] The Young's modulus of glass was tested by ultrasonic echo analysis using UMS-100 ultrasonic material characterization system.

[0135] Stress parameter test

[0136] Surface stress test: CS_50 and DOL_0 surfaces were tested using the stress meter SLP-2000 from Luceo (Japan Orihara).

[0137] The test conditions are: light source wavelength 518nm, SOC = 28.6 (nm / cm) / MPa, refractive index = 1.51, exposure time: 5000usec. When testing CS_50 and DOL_0, you need to first drop a conductive liquid on the stress meter, then wipe the glass sample to be tested clean, place it on the test path, and test its stress value. SLP-2000 uses a conductive liquid with a refractive index of 1.51.

[0138] CT_LD is calculated as follows:

[0139]

[0140] Where: t represents the thickness of the glass sheet, in mm; DOL_0 represents the depth of the compressive stress layer, in μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in the calculation, in MPa. It should be understood that in the calculation formula of the tensile stress linear density, (1000t / 2-DOL_0) is to substitute the data for the calculation and obtain the calculation result, and the unit does not participate in the calculation.

[0141] CT_LD max Test: In this application, a 100wt% sodium nitrate salt bath at 450°C was used as the test CT_LD max The salt bath condition is adopted, and the SLP-2000 stress meter is used as the test instrument for testing the tensile stress linear density CT_LD. The specific method is: the substrate glass sample to be tested is placed in a 100wt% sodium nitrate salt bath at 450°C for chemical strengthening. During the strengthening period, the glass sample is taken out every 0.5h to test the CT_LD value inside it. After each glass sample is taken out for testing, the glass sample is immediately placed in the salt bath and continued to be strengthened. When the next test time point is reached, the glass sample is taken out for testing again, and the above test process is repeated to record the tested CT_LD value. When it is found that the measured CT_LD value begins to decrease after increasing to a certain value m, it is determined that the value m is the maximum tensile stress linear density CT_LD that can be obtained by strengthening the substrate glass sample in the salt bath condition, that is, in a 100wt% sodium nitrate salt bath at 450°C. max .

[0142] Bifurcation threshold test: First test the substrate glass with a thickness of 0.7 mm corresponding to a certain glass formula, perform ion exchange in a certain salt bath, and obtain the maximum value of the tensile stress linear density CT_LD max Then, chemically strengthened glass samples with different CT_LD were strengthened under the salt bath conditions, for example, CT_LD ranged from 30000 MPa / mm to CT_LD max, with an increase of about 1000MPa / mm, 1500MPa / mm or 2000MPa / mm, CT_LD is obtained by testing with an SLP-2000 stress meter. For example, in this application, the substrate glass with a thickness of 0.7mm corresponding to the glass formula to be tested is strengthened in a 100wt% sodium nitrate salt bath at 450°C to obtain chemically strengthened glass samples with CT_LD of about 30000MPa / mm, about 31000MPa / mm, about 32000MPa / mm, about 33000MPa / mm, about 34000MPa / mm, and about 36000MPa / mm, respectively. These chemically strengthened glass samples are then subjected to immediate fracture tests in order of CT_LD values ​​from low to high. The center point of the chemically strengthened glass sample is used as the failure point, and a "stress release device" is used to cause cracks to form at the failure point. A chemically strengthened glass sample with crack bifurcation is selected, and the minimum CT_LD value of the chemically strengthened glass sample with crack bifurcation is used as the bifurcation threshold of the chemically strengthened glass prepared from the base glass of the formula.

[0143] Immediate fracture test: The center point of the chemically strengthened glass sample is used as the breaking point, and a "stress release device" is used to generate cracks at the breaking point, so that the cracks extend under the action of the internal tensile stress, rather than generating starbursts due to excessive impact force. When the crack of the chemically strengthened glass bifurcates, the minimum tensile stress linear density value of the chemically strengthened glass sample is the bifurcation threshold. A certain number of substrate glass products are strengthened under the same salt bath conditions and different ion exchange times to obtain glass samples with different tensile stress linear densities. According to the tensile stress linear density values ​​from low to high, fracture tests are performed on the multiple glass samples obtained by strengthening. After the immediate fracture test, check whether the crack of the glass sample bifurcates, find the glass samples with crack bifurcations, and determine the minimum tensile stress linear density (CT_LD) value corresponding to these glass samples, which is the bifurcation threshold of the chemically strengthened glass corresponding to the substrate glass.

[0144] The stress relief device Figure 1 , where 1 represents the height adjustment rail, 2 represents the start adjustment rail, 3 represents the indenter, and 4 represents the chemically strengthened glass sample; the device uses pneumatic impact, and the probe uses a Vickers diamond indenter and is fixed with a rail to ensure that the indenter impacts the glass surface vertically. It is also equipped with a pressure sensor, which controls the impact force in combination with air pressure regulation, so that the damage point only induces delayed fracture or only extends two cracks instead of generating starbursts, thereby minimizing the influence of external forces on the damage state. In the immediate fracture experiment, the crack needs to be extended as Figure 2 As shown in a or b in Figure 2 As shown in c.

[0145] Acid resistance test

[0146] The acid resistance in this application refers to the resistance of glass to hydrochloric acid corrosion, and the acid resistance of glass is characterized by the corrosion amount per unit area.

[0147] Prepare the glass into 50mm×50mm×0.7mm (specification size), first weigh it on a balance with an accuracy of 0.0001g, then put it into a 5wt% hydrochloric acid solution and keep it at 95℃ for 24h. After completion, take out the glass, weigh it again, and subtract the weight of the unetched part to get the weight difference M (in g), and calculate the area S (in cm) of the front and back sides of the glass. 2 ), the amount of erosion per unit area = M / S.

[0148] Crystallization upper limit temperature test

[0149] The upper limit temperature of crystallization refers to the highest temperature at which the substrate glass produces crystallization. Above this temperature, the substrate glass will not precipitate crystals.

[0150] The substrate glass is broken into small pieces of 2mm-5mm in size, and then placed in the long quartz tank and filled.

[0151] The gradient furnace of model JKZC-XJY01 is set to a temperature range, such as a temperature range of 1050-1225°C, and at least 6 temperature points are selected from high to low in each temperature range.

[0152] After the gradient furnace reaches the preset temperature range, place the long quartz tank with the sample into the gradient furnace so that the six temperature points correspond to the glass samples at the six positions in the long quartz tank. Figure 3 After placing the long quartz tank in a gradient furnace and keeping it at a constant temperature for 60-70 minutes, the long quartz tank is taken out.

[0153] Observe the glass samples at different positions in the long quartz tank. If the glass sample is devitrified or foggy, it is determined that the glass sample at that position has crystallized. If the glass sample is completely transparent, it is determined that the glass sample at that position has not crystallized. Figure 3 , Figure 3 In the long quartz cell, the upper area is a completely transparent sample, the lower area is a devitrified sample, and there is a part of foggy sample between the completely transparent sample and the devitrified sample. When observing, you can use tools such as a magnifying glass, a microscope, etc.

[0154] Determination of the upper limit temperature of crystallization: The upper limit temperature range of crystallization is between the temperature point corresponding to the completely transparent sample and the temperature point corresponding to the adjacent devitrified or foggy sample. The average value of the two temperature points is taken as the upper limit temperature of crystallization.

[0155] If all the glass samples in the long quartz trough crystallize within the temperature range set by the gradient furnace, the upper limit temperature of the gradient furnace temperature range is reset, and the upper limit temperature of crystallization of the glass samples is measured; if all the glass samples in the long quartz trough do not crystallize within the temperature range set by the gradient furnace, the lower limit temperature of the gradient furnace temperature range is reset, and the upper limit temperature of crystallization of the glass samples is measured.

[0156] Viscosity corresponding to the upper limit of crystallization

[0157] Prepare more than 250 g of substrate glass and place it in a corundum crucible or a platinum crucible.

[0158] The RSV-1600RT high temperature viscometer is turned on to increase the temperature, and then the crucible containing the substrate glass is placed in the heating test area. The temperature is generally increased to the melting temperature (the melting temperature is the temperature when the glass viscosity is 100 poise), and the temperature can be increased to 1680°C at the highest.

[0159] The temperature was raised to 1580°C to melt the glass. After keeping the temperature for 20 minutes, the platinum rotor probe was placed in the substrate glass to test the viscosity of the substrate glass. The temperature was then lowered at a rate of 2°C / min, and the viscosity of the substrate glass was continuously tested until the viscosity reached about 100,000 poise. The test was completed and the platinum rotor probe was taken out. The instrument recorded the test temperature and test viscosity of the substrate glass at the same time and output the data. The present application is further described below through specific embodiments.

[0160] Example 1

[0161] Accurately weigh the raw materials according to the following ratio: SiO2 63.00mol% 、 Al2O3 11.00mol%, Y2O3 2.00mol%, La2O3 2.00mol%, MgO 5.00mol%, Na2O 5.00mol%, Li2O 10.00mol%, ZrO2 2.00mol%; the total mass of the above raw materials is 1600g, 0.4wt% of clarifier sodium chloride (6.4g sodium chloride) is added, and the mixture is fully mixed to obtain a mixture.

[0162] The mixture is placed in a platinum crucible, heated to 1650°C in a high-temperature melting furnace to melt for 10 hours, then poured into a molding mold to cool and shape, cooled to 800°C, placed in an annealing furnace, and annealed at 560°C for 2000 minutes; then cooled to 500°C within 300 minutes, kept warm for 300 minutes, then cooled to 400°C within 300 minutes, kept warm for 300 minutes, then cooled to 300°C within 300 minutes, kept warm for 300 minutes, and then cooled to 300°C within 300 minutes, and kept warm for 300 minutes, to achieve gradient slow cooling; then cooled to room temperature with the furnace to obtain glass bricks; the obtained glass bricks are shaped and cut using a multi-wire cutting machine to obtain glass sheets with a thickness of 0.7 mm, such as 50 mm × 50 mm × 0.7 mm (specification size), 158.8 mm × 72.8 mm × 0.7 mm, etc.; precision machining (CNC), thinning, and polishing are performed to obtain the substrate glass of chemically strengthened glass.

[0163] The obtained substrate glass is subjected to two-step chemical strengthening to obtain chemically strengthened glass; wherein, the first step of chemical strengthening is chemical strengthening treatment in a 100wt% NaNO3 salt bath at 450°C for 5 hours; the second step of chemical strengthening is chemical strengthening treatment in a 100wt% KNO3 salt bath at 450°C for 1 hour.

[0164] Embodiment 2-6

[0165] Except for adjusting the raw material ratio and chemical strengthening treatment conditions as shown in Table 1, the rest is the same as Example 1.

[0166] Comparative Examples 1-5

[0167] Except for adjusting the raw material ratio and chemical strengthening treatment conditions as shown in Table 1, the rest is the same as Example 1.

[0168] The performance tests were performed on the base glass and the chemically strengthened glass of the chemically strengthened glass prepared in Examples 1-6 and Comparative Examples 1-5, respectively.

[0169] The relevant parameters of the substrate glass and the chemically strengthened glass in the above-mentioned Examples 1-5 and Comparative Examples 1-6 are shown in Tables 1 and 2 below.

[0170]

[0171]

[0172] It can be seen from Table 1 and Table 2 above that the content of each component and the content relationship between the components of Examples 1-6 are within the scope of the present application, and the Young's modulus of the substrate glass is higher than 95 GPa; in terms of acid resistance, the erosion amount of the substrate glass in a 5wt% HCl solution at 95°C for 24 hours is ≤7 mg / cm 2In terms of stress performance, the maximum tensile stress linear density CT_LD that can be obtained by ion exchange of 0.7mm thick substrate glass is max All of them are higher than 56000MPa / mm, and the bifurcation threshold of the substrate glass is higher than 50000MPa / mm; in addition, the upper limit crystallization temperature of the substrate glass is ≤1310℃, and the viscosity corresponding to the upper limit crystallization temperature is greater than or equal to 10 2.2 dPa·s, which can meet the continuous melting and casting production processes.

[0173] The content of Y2O3+La2O3 in Comparative Example 1 is relatively high, which is not within the scope of this application, resulting in poor acid resistance of the substrate glass and failing to meet the requirements; in addition, the upper limit of crystallization temperature is relatively high, >1360°C, and the corresponding viscosity of the upper limit of crystallization is <10 2.0 dPa·s, resulting in poor mass production performance of glass.

[0174] In Comparative Example 2, La2O3 / (Y2O3+La2O3) is too high and is not within the scope of this application, resulting in a higher upper limit temperature of crystallization of the substrate glass, which is 1355°C. The corresponding viscosity of the upper limit of crystallization is less than 10 2.0 dPa·s, resulting in poor mass production performance of glass.

[0175] The content of Y2O3+La2O3 in Comparative Example 3 is relatively low and is not within the scope of this application, resulting in a relatively high upper crystallization temperature of the substrate glass, >1360°C, and a corresponding viscosity of <10 2.0 dPa·s, resulting in poor mass production performance of glass.

[0176] The contents of SiO2 and Al2O3 in Comparative Example 4 are not within the scope of the present application, and the ratio of Al2O3 / SiO2 is not within the scope of the present application, resulting in a higher upper limit crystallization temperature of the substrate glass, >1360°C, and a corresponding viscosity of 10. 2.1 dPa·s, resulting in poor mass production performance of the glass; and the acid resistance is very poor and does not meet the requirements.

[0177] The content of Y2O3+La2O3 in Comparative Example 5 is relatively low and is not within the scope of the present application, resulting in a low Young's modulus of the substrate glass that does not reach 95 GPa, and a bifurcation threshold of ≤49000 MPa / mm.

[0178] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A chemically strengthened glass, characterized in that: The tensile stress layer of the chemically strengthened glass comprises the following components, measured in molar percentage of oxides: SiO2 60.0-70.0mol%; Al2O3 8.0-15.0mol%; MgO 1.0-8.0 mol%; Li2O 7.0-12.0mol%; Na2O 2.0-5.0mol%; and Y2O3 and La2O3; Among them, Y2O3+La2O3 is 4.0-8.0mol%, and La2O3 / (Y2O3+La2O3) is 0.25-0.65; the CS_50 of the chemically strengthened glass is 100MPa-150MPa; and the thickness t of the chemically strengthened glass is 0.4-2.0mm.

2. The chemically strengthened glass according to claim 1, wherein: The CS_50 of the chemically strengthened glass is 105 MPa-150 MPa, preferably 110 MPa-140 MPa.

3. The chemically strengthened glass according to claim 1 or 2, characterized in that: The DOL_0 of the chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the chemically strengthened glass.

4. The chemically strengthened glass according to claim 1 or 2, characterized in that: The CT_LD of the chemically strengthened glass is 45000MPa / mm-60000MPa / mm, preferably 45000MPa / mm-57000MPa / mm; CT_LD refers to the ratio of the definite integral of the tensile stress curve of the chemically strengthened glass to the thickness of the chemically strengthened glass, which is recorded as the tensile stress line density.

5. A method for preparing the chemically strengthened glass according to any one of claims 1 to 4, comprising the following steps: (1) selecting raw material components according to the composition of the substrate glass, mixing them, melting and forming them, and then cooling and annealing them to obtain the substrate glass; (2) chemically strengthening the substrate glass to obtain chemically strengthened glass; The substrate glass comprises the following components in terms of molar percentage of oxides: SiO2 60.0-70.0mol%; Al2O3 8.0-15.0mol%; MgO 1.0-8.0 mol%; Li2O 7.0-12.0mol%; Na2O 2.0-5.0mol%; and Y2O3 and La2O3; in, Y2O3+La2O3 is 4.0-8.0 mol%.

6. The method for preparing chemically strengthened glass according to claim 5, characterized in that: The substrate glass further comprises the following components in terms of molar percentage of oxides: K2O 0-2.0mol%; ZrO2 0-2.0mol%; B2O3 0-5.0mol%; P2O5 0-5.0mol%; CaO 0-8.0 mol%; SrO 0-3.0 mol%.

7. The method for preparing chemically strengthened glass according to claim 5 or 6, characterized in that: The chemical strengthening in step (2) includes single-step chemical strengthening or multi-step chemical strengthening.

8. The method for preparing chemically strengthened glass according to claim 7, characterized in that: The single-step chemical strengthening adopts a mixed salt bath containing NaNO3 and KNO3, preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%; and / or the temperature of the single-step chemical strengthening is 380℃-500℃, and more preferably the ion exchange time of the single-step chemical strengthening is 3h-10h.

9. The method for preparing chemically strengthened glass according to claim 7, characterized in that: The multi-step chemical strengthening includes two-step chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 in the salt bath is 70-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, and preferably the content of KNO3 in the salt bath is 60-100wt%; and / or the temperature of the first step of chemical strengthening is 380℃-500℃, and the ion exchange time is preferably 3h-10h; and / or the temperature of the second step of chemical strengthening is 380℃-500℃, and the ion exchange time is preferably 1h-10h.

10. A glass device, characterized in that: A chemically strengthened glass comprising the chemically strengthened glass according to any one of claims 1 to 4 or a chemically strengthened glass prepared by the method for preparing the chemically strengthened glass according to any one of claims 5 to 9.

11. An electronic device, characterized in that: A chemically strengthened glass comprising the chemically strengthened glass according to any one of claims 1 to 4 or a chemically strengthened glass prepared by the method for preparing the chemically strengthened glass according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • High-modulus glass fiber composition as well as glass fiber and composite material thereof

    CN105731813A

  • Lithium aluminum silicon glass, lithium aluminum silicon chemically strengthened glass and preparation method and application thereof

    CN110240419A

  • Glass, chemically strengthened glass, and cover glass

    CN114096489A

  • Master glass, chemically strengthened glass, 3D hot bending glass and hot bending strengthened glass

    CN116081945A

  • Glass, chemically strengthened glass, and electronic device comprising chemically strengthened glass

    CN116332504A